Sports: As an Appliance of Incorporation toward Malaysian Society - Haji Omar, Abdul Hafidz; Awang Hj. Hamid, Dayang Hjh. Tiawa; Islam, Md. Rajibul (Science Publications (SCIPUB), 2010)
Problem statement: This research investigated the elements of sport that led to social integration in Malaysian society and identified the steps taken to achieve social integration through sports. As a multi racial country, Malaysia consisting of three major races, the Malays, Chinese and Indians were seen practicing the sport cultures that were inherited by their forefathers. History shows that colonization by the western powers i.e. the Portuguese, Dutch and the British were claimed to have great impact on the segregation of these three races. The Chinese congregated around the town areas specially controlling the tin mines industry, the Malays were seen mostly in the paddy plantation industry while the Indians dominating the rubber plantation industry. The differences are not only seen in their choice of occupation and living areas but even seen in their choice of sporting activities. With such differences and diversity in beliefs and practices one would think it would be difficult for these different Races to work together as a team. Approach: To clarify this statement, the study employed an ethnographic approach to assist the case study which was conducted on 30 athletes, selected using propulsive sampling, 10 from each of the 3 main races. The data collecting methods used were interviews, observation and document analysis. Results: Triangulation Technique helps to support the validity of the findings. Its aims to capture the athletes’ cultural practices and investigated whether the implementation of the national sports policy is effective in contributing towards the integration of the different races in Malaysia. Conclusion/Recommendations: The findings of the study showed some very interesting results which further strengthen the claims that sports not only can be an agent of integration but also acts as a catalyst to bring people of different races to compete with one goal in mind, striving for the nation rather than for one’s race glory and victory.